Urbanisasi dan Modernisasi (Studi Tentang Perubahan Sistem Nilai Budaya Masyarakat Urban di Pangkalan Kerinci Kabupaten Pelalawan) - Hidayat Syah (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2013)
Urbanization is the movement of people from rural to urban. That change took effect on views and systems of traditional village culture and patnership familiarship the modernist view that is more individualistic, independent, and competitive. Change is only possible if the villagers who did urbanization have an attitude of openness towards the new atmosphere and able to change their mind set on being a fatalist (jabariah) to independence (qadariah), and was able to find the channels proper adjustment.